Search for direct CP violation in charged charmless B → PV decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review, 2023)
Measurements of 𝐶⁢𝑃 asymmetry in charmless 𝐵→𝑃⁢𝑉 decays are presented, where 𝑃 and 𝑉 denote a pseudoscalar and a vector meson, respectively. Five different 𝐵→𝑃⁢𝑉 decays from four final states, 𝐵±→𝜋±⁢𝜋+⁢𝜋−, 𝐵±→𝐾±⁢𝜋+⁢𝜋−, 𝐵±→𝐾±⁢𝐾+⁢𝐾− and 𝐵±→𝜋±⁢𝐾+⁢𝐾− are analyzed. The measurements are based on a method that does not require full amplitude analyses, and are performed using proton-proton collision data at a center-of-mass energy of 13 TeV collected by LHCb between 2015 and 2018, corresponding to an integrated luminosity of 5.9 fb−1. In the 𝜋+⁢𝜋− 𝑃-wave, in the region dominated by the 𝐵±→𝜌⁢(770)0⁢𝐾± decay, a 𝐶⁢𝑃 asymmetry of 𝐴𝐶⁢𝑃=+0.150±0.019±0.011 is measured, where the first uncertainty is statistical and the second is systematic. This is the first observation of 𝐶⁢𝑃 violation in this process. For the other four decay channels, in regions dominated by the 𝐵±→𝜌⁢(770)0⁢𝜋±, 𝐵±→(¯ )𝐾⁢ *⁢(892)0⁢𝜋±, 𝐵±→(¯ )𝐾⁢ *⁢(892)0⁢𝐾± and 𝐵±→𝜙⁡(1020)⁢𝐾± decays, 𝐶⁢𝑃 asymmetries in the 𝑃-wave compatible with zero are measured.